Fuzzy Logic and Information Fusion To commemorate the 70th birthday of Professor Gaspar Mayor - Calvo Sánchez, Tomasa; Torrens Sastre, Joan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book offers a timely report on key theories and applications of soft-computing. Written in honour of Professor Gaspar Mayor on his 70th birthday, it primarily focuses on areas related to his research, including fuzzy binary operators, aggregation functions, multi-distances, and fuzzy consensus/decision models. It also discusses a number of interesting applications such as the implementation of fuzzy mathematical morphology based on Mayor-Torrens t-norms. Importantly, the different chapters, authored by leading experts, present novel results and offer new perspectives on different aspects of Mayor's research. The book also includes an overview of evolutionary fuzzy systems, a topic that is not one of Mayor's main areas of interest, and a final chapter written by the Spanish pioneer in fuzzy logic, Professor E. Trillas. Computer and decision scientists, knowledge engineers and mathematicians alike will find here an authoritative overview of key soft-computing concepts and techniques.
Gaspar Mayor: A Prolific Career on Fuzzy Sets and Aggregation Functions -- Smooth Finite T-Norms and Their Equational Axiomatization -- Associative Copulas: A Brief Survey -- Powers with Respect to t-norms and t-conorms and Aggregation Functions -- Modus Tollens on Fuzzy Implication Functions Derived from Uninorms -- A Survey of Atanassov's Intuitionistic Fuzzy Relations -- On Weighting Triangles Using Fuzzy Relations and its Application to Aggregation Functions -- New Advances in the Aggregation of Asymmetric Distances.The Bounded Case -- Multidistances and Dispersion Measures -- Soft Consensus Models in Group Decision Making -- Relation Between AHP and Operators Based on Different Scales -- Evolutionary Fuzzy Systems: A Case Study in Imbalanced Classification -- Mayor-Torrens t-norms in the Fuzzy Mathematical Morphology and their Applications -- A Short Dialogue Concerning "what is" and "what is not" with Imprecise Words.
Keywords: Computational intelligence; Data mining; Artificial intelligence; Computational linguistics; Computational Intelligence; Data Mining and Knowledge Discovery; Artificial Intelligence; Computational Linguistics